Effect of cryotherapy on post-exercise cardiac autonomic recovery in mixed martial arts (MMA) fighters: A Randomized Clinical Trial (Research, Society and Development, 2022)
Background: Cryotherapy brings benefits for muscle recovery and reduction of lactate thresholds in fighters; however, the effect of cryotherapy on the autonomous cardiac recovery (ACR) of wrestlers is not yet defined in the scientific literature. Objective: To analyze the effect of cryotherapy on ACR after simulated combat exercise in mixed martial arts (MMA) fighters. Methods: Crossover randomized clinical trial with a sample of 17 MMA fighters (male, age >18 years). There was simulated combat of three rounds of MMA; each round lasted 5-min, there were the 60s between rounds. ACR was assessed by resting heart rate (RHR), which was monitored by a portable Polar-FT1® device. We measured RHR in the interval between the rounds at the 30s and 60s of rest in the conditions: without cryotherapy (Control), application of an ice pack in the thoracic region (TC); Immersion of feet in ice water (FC). Results: At 30-s of RHR, the control condition was better than FC to reduce RHR in rounds 1 and 2 (p